2021
DOI: 10.3390/agriculture11111114
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Technical Efficiency in the EU Dairy Farms

Abstract: This paper aims to analyse the technical efficiency (TE) of dairy farms and find its determinants. To accomplish this problem, the Stochastic Frontier Analysis was applied. The data were obtained from the Farm Accountancy Data Network database for dairy farms (TF15-45—Specialist dairying) for 2004–2019. Dairy farms were divided into four clusters according to their physical size (number of livestock units per farm) and economic size (standard output per farm). The largest farms by physical and economic size ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Many studies on the dairy cattle sector use the same input and/or output variables in their efficiency models. Indicatively, gross revenue has been used as output by Náglová and Rudinskaya [18], Theodoridis et al [19], Theodoridis and Ragkos [23], Mitsopoulos et al [25], and Spička and Smutka [34]; human labor has been used as input in Alvarez and Arias [17], Náglová and Rudinskaya [18], Madau et al [21], Theodoridis and Ragkos [23], Siafakas et al [24], Mitsopoulos et al [25] and Areal [35]; while variable capital cost and fixed capital cost have been used as inputs by Alvarez and Arias [17], Náglová and Rudinskaya [18], Madau et al [21],. Theodoridis and Ragkos [23], Mitsopoulos et al [25], Areal [35] and Kovács and Szücs [36].…”
Section: Data Envelopment Analysis Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies on the dairy cattle sector use the same input and/or output variables in their efficiency models. Indicatively, gross revenue has been used as output by Náglová and Rudinskaya [18], Theodoridis et al [19], Theodoridis and Ragkos [23], Mitsopoulos et al [25], and Spička and Smutka [34]; human labor has been used as input in Alvarez and Arias [17], Náglová and Rudinskaya [18], Madau et al [21], Theodoridis and Ragkos [23], Siafakas et al [24], Mitsopoulos et al [25] and Areal [35]; while variable capital cost and fixed capital cost have been used as inputs by Alvarez and Arias [17], Náglová and Rudinskaya [18], Madau et al [21],. Theodoridis and Ragkos [23], Mitsopoulos et al [25], Areal [35] and Kovács and Szücs [36].…”
Section: Data Envelopment Analysis Modelmentioning
confidence: 99%
“…Indeed, Musliu et al [40] estimated the technical efficiency of 57 farms in Kosovo using SFA and reported a high TE score of 0.95, a result that is in accordance with our findings. In addition, Náglová and Rudinskaya [18], based on panel data obtained from the Farm Accountancy Data Network (FADN) database covering EU member states (no data available for Cyprus and Greece) for 2004-2019, calculated an average TE score of 0.900 for EU-27 members. Náglová and Rudinskaya [18] used the stochastic frontier approach (SFA) for the estimation of efficiency, an approach that does not attribute any deviation from the efficient frontier entirely to inefficiencies [30].…”
Section: Efficiency Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In the EU, dairy production is a core agricultural sector, and its market‐driven transformation has been key in the CAP, even before the abolition of the milk quota system in 2015 (Jongeneel, 2011). The latter may have contributed to improved technical efficiency (Náglová & Rudinskaya, 2021) and increased productivity (Čechura et al., 2021). Nevertheless, it has also brought new and significant challenges concerning the role of dairy production in terms of rural development (Stuiver & Wiskerke, 2004; van der Ploeg, 2008) and transformed the socioeconomic structures of the dairy sector (Butler & Holloway, 2016; Vik et al., 2019).…”
Section: Introductionmentioning
confidence: 99%